Percepción psicológica del color en la Generación Z en los rubros tecnología y alimentos. - Reinoso Calle, Sebastian Alberto (2025)
This research aims to analyze how color psychology influences the perception and purchasing decisions of Generation Z, with a particular focus on technological and food-related products. The study was approached through a mixed-methods design that combined semi-structured interviews, structured surveys, and visual analysis sheets to obtain both qualitative and quantitative insights into the phenomenon. The results show that color plays a decisive role in how Generation Z interprets, evaluates, and selects products. In the food industry, warm colors such as red, orange, and yellow are perceived as appetizing and stimulating, evoking positive sensations of energy and flavor. In contrast, in technological products, cool and neutral tones such as black, gray, and blue predominate, conveying sensations of modernity, trust, and elegance. Additionally, chromatic coherence between packaging, product, and brand was found to enhance visual recall and improve quality perception, becoming a key factor in fostering brand loyalty among Generation Z. Goethe’s theory of color was essential in understanding emotional responses to chromatic stimuli, and its methodological application enabled a deeper interpretation of the collected data. Ultimately, color is not merely an aesthetic component but a visual language that communicates values, emotions, and attributes directly influencing Generation Z’s purchasing decisions.